Graft-Versus-Host Disease Amelioration by Human Bone Marrow Mesenchymal Stromal/Stem Cell-Derived Extracellular Vesicles Is Associated with Peripheral Preservation of Naive T Cell Populations. (27th December 2017) - Fujii, Sumie; Miura, Yasuo; Fujishiro, Aya; Shindo, Takero; Shimazu, Yutaka; Hirai, Hideyo; Tahara, Hidetoshi; Takaori-Kondo, Akifumi; Ichinohe, Tatsuo; Maekawa, Taira
Abstract : A substantial proportion of patients with acute graft-versus-host disease (aGVHD) respond to cell therapy with culture-expanded human bone marrow mesenchymal stromal/stem cells (BM-MSCs). However, the mechanisms by which these cells can ameliorate aGVHD-associated complications remain to be clarified. We show here that BM-MSC-derived extracellular vesicles (EVs) recapitulated the therapeutic effects of BM-MSCs against aGVHD. Systemic infusion of human BM-MSC-derived EVs prolonged the survival of mice with aGVHD and reduced the pathologic damage in multiple GVHD-targeted organs. In EV-treated GVHD mice, CD4+ and CD8+ T cells were suppressed. Importantly, the ratio of CD62L-CD44+ to CD62L + CD44- T cells was decreased, suggesting that BM-MSC-derived EVs suppressed the functional differentiation of T cells from a naive to an effector phenotype. BM-MSC-derived EVs also preserved CD4 + CD25 + Foxp3+ regulatory T cell populations. In a culture of CD3/CD28-stimulated human peripheral blood mononuclear cells with BM-MSC-derived EVs, CD3+ T cell activation was suppressed. However, these cells were not suppressed in cultures with EVs derived from normal human dermal fibroblasts (NHDFs). NHDF-derived EVs did not ameliorate the clinical or pathological characteristics of aGVHD in mice, suggesting an immunoregulatory function unique to BM-MSC-derived EVs. Microarray analysis of microRNAs in BM-MSC-derived EVs versus NHDF-derived EVs showed upregulation of miR-125a-3p and downregulation of cell proliferative processes, as identified by Gene Ontology enrichment analysis. Collectively, our findings provide the first evidence that amelioration of aGVHD by therapeutic infusion of BM-MSC-derived EVs is associated with the preservation of circulating naive T cells, possibly due to the unique microRNA profiles of BM-MSC-derived EVs. Abstract : Systemic infusion of human bone marrow mesenchymal stromal/stem cell (BM-MSC)-derived extracellular vesicles (EVs) prolongs the survival of mice with graft-versus-host disease (GVHD) and reduces the clinical symptoms and pathologic damage in multiple GVHD-targeted organs. CD4 + CD25 + Foxp3+ regulatory T cells and CD62L + CD44− naive T cells are preserved in peripheral blood of GVHD mice treated with BM-MSC-derived EVs. Microarray analysis of microRNAs in BM-MSC-derived EVs shows upregulation of miR-125a-3p and downregulation of cell proliferative processes, as identified by Gene Ontology enrichment analysis.